A Spatio-Temporal Evaluation of Water Resilience and Urban Metabolism in Informal Settlements using Remote Sensing - Ramdan Pano Anwar; Kollányi László (Jurnal Peweka Tadulako, 2026)
Informal settlements face layered challenges of environmental degradation, governance fragmentation, and infrastructure inequity. This study aims to evaluate the spatial-temporal dynamics of environmental and hydrological stress within these settlements to inform targeted upgrading strategies. Utilizing Google Earth Engine and QGIS, multi-temporal and multi-spectral satellite imagery from Landsat 8/9 and Sentinel-2 (2015–2024) was processed to map ecological stress and urban expansion in Makassar, Indonesia. The methodological approach includes the calculation and zonal statistics extraction of key indices: Normalized Difference Vegetation Index (NDVI), Normalized Difference Built-up Index (NDBI), Land Surface Temperature (LST), and Moisture Stress Index (MSI). The findings reveal a severe ecological gradient characterized by a continuous downward trend in vegetation (NDVI < 0.2) and a corresponding escalation of surface impermeability in informal zones. This urban densification directly driven thermal intensification, with LST peaking above 34°C, and extreme moisture stress exceeding critical resilience thresholds (MSI > 0.9). Ultimately, this integrated geospatial diagnostic empowers the SLAIS Framework to transition landscape architecture into an operable, evidence-based discipline capable of targeting interventions where metabolic pathology is greatest.